Термопружний згин локально нагрітої композитної пластинки - Жидик, Уляна (КІНПАТРІ ЛТД, 2013)
The dynamic behavior of composite plates to rapid heating is investigated. A closed form solutions are presented for simply supported rectangular cross-ply and angle-ply laminated plates. Numerical results are finally presented and discussed.
Thermoelastic bending of locally heated composite plate